Strategi Dan Model Kepemimpinan Dalam Mencapai Keberhasilan di Dunia Pendidikan - aisunu, Khoirotun Nisa'; Muttaqin, M. Imamul (STAIN Madina Press, 2024)
Education is a fundamental element in nation building, but the quality of education in many countries still does not meet expected standards. Leadership plays a key role in efforts to improve the quality of education, where effective leaders can increase teacher motivation and student performance. This research aims to examine effective leadership strategies and models in the world of education. With a qualitative approach based on literature study, data was collected through document analysis in the form of journal articles, books and research reports. The data analysis process uses thematic analysis to identify main themes. Validity and reliability are maintained through source triangulation. The research results show that leadership strategies which include bartering, building, binding, and bonding are able to encourage the achievement of educational goals. Leadership models such as authoritarian, democratic, charismatic, transformational, and spiritual are also identified as significant approaches in leading educational institutions. Factors such as morality, organizational culture, and rewards were found to be the main elements of successful educational leadership. Thus, effective leadership is expected to support the optimal achievement of national education goals.